2008
DOI: 10.1111/j.1469-8749.2008.03000.x
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy in cerebral palsy: an update

Abstract: This paper clarifies and updates some issues of life expectancy in cerebral palsy. These are: (1) the definition of life expectancy and how it is calculated; (2) the secular trends that have occurred since the data for the 1998 paper were collected; (3) revised estimates reflecting improvements of some of the analytical methods and statistics provided in that paper; (4) comparison of life expectancies among countries; (5) issues regarding quality of care; and (6) consideration of prospective life expectations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
133
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 17 publications
2
133
0
6
Order By: Relevance
“…25 In extrapolating long-term costs, we assumed that the modelled disability outcomes would have an adverse effect on life expectancy. For this reason, mortality rates reported for preterm infants with cerebral palsy were used to model survival in disabled infants, 26,27 while standard UK life tables were used to model survival in infants without disability.…”
Section: Clinical Inputsmentioning
confidence: 99%
“…25 In extrapolating long-term costs, we assumed that the modelled disability outcomes would have an adverse effect on life expectancy. For this reason, mortality rates reported for preterm infants with cerebral palsy were used to model survival in disabled infants, 26,27 while standard UK life tables were used to model survival in infants without disability.…”
Section: Clinical Inputsmentioning
confidence: 99%
“…The recent extension of this data to extend to age 21 suggests that deterioration in function may begin in more impaired children from around age 8 (Hanna et al 2009). Such similar curves are not yet available for adults, although trends in data from the large studies by Strauss and colleagues suggest a similar profile of decline (Strauss, Ojdana, Shavelle and Rosenbloom 2004; Strauss et al 2008). A recent systematic review of 16 studies reporting gait decline in adults found variation in the incidence of decline, but with most studies reporting decline affecting around 30% or more of the study participants .…”
Section: Mobility Decline and Associated Factorsmentioning
confidence: 99%
“…Adults with CP are a growing community who are now recognised as outnumbering children 3:1 in some countries (Access Economics 2008). With advances in healthcare, it is now usual for those who walk during childhood to have a relatively normal life expectancy (Strauss, Brooks, Rosenbloom and Shavelle 2008). Over recent times, the need to consider CP as a lifespan, rather than childhood condition has been highlighted, with particular interest in the reported difficulties that emerge during the adult years (Tosi et al 2009; .…”
Section: Introductionmentioning
confidence: 99%
“…17 Epilepsy and degree of mental retardation* can further adversely affect survival. 16,18 The purpose of the present study was to determine whether ongoing management of hypertonia with ITB is associated with an increase in the long-term risk of mortality in persons with CP.…”
mentioning
confidence: 99%
“…Mortality rates are higher, and survival probabilities lower, for those with more severe CP, severity being measured by simple functional variables including gross and fine motor skills (ambulation, rolling, or crawling) and feeding ability. [12][13][14][15][16] Comparisons of survival rates in persons with CP in the USA, the UK, and Australia that have accounted for these basic functional vari- The purpose of the present study was to determine whether ongoing management of hypertonia with ITB is associated with an increase in the long-term risk of mortality in persons with CP. …”
mentioning
confidence: 99%